1988
DOI: 10.1007/bf00464632
|View full text |Cite
|
Sign up to set email alerts
|

Immune status in patients with Meniere's disease

Abstract: Sera of 164 patients with classical Meniere's disease were screened for autoantibodies, immune complexes and HLA status. Increased thyroid microsomal antibodies were significant in those patients in the 40- to 60-year age range. Raised IgM complexes and C1q component of complement were significant in all age groups. Low levels of IgA complexes were a consistent finding and were significantly lower in the HLA Cw7 group. Patients with migraine had no increased incidence of immune disturbances.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

1995
1995
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 18 publications
1
29
0
1
Order By: Relevance
“…thyroid dysfunction [Brenner et al, 2004], increased microsomal thyroid antibodies [Evans et al, 1988], and a significant level of autoantibodies (overall antithyroid antibody positivity) [Fattori et al, 2008]. In a recent report a significant association between MD and autoantibody increments, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…thyroid dysfunction [Brenner et al, 2004], increased microsomal thyroid antibodies [Evans et al, 1988], and a significant level of autoantibodies (overall antithyroid antibody positivity) [Fattori et al, 2008]. In a recent report a significant association between MD and autoantibody increments, e.g.…”
Section: Introductionmentioning
confidence: 97%
“…The possible association between AITD and MD has been postulated since over 30 years, although it is still a controversial issue. At the beginning of the 1980s, Kinney [1980] and Meyerhoff [1981] excluded a relationship between thyroid dysfunction and MD [Kinney, 1980;Meyerhoff et al, 1981]; however, Evans et al [1988] showed that antithyroid microsome antibodies occurred in 17% of 150 MD patients [Evans et al, 1988] and this association was recently confirmed [Brenner et al, 2004;Fattori et al, 2008]. Interestingly, Evans et al [1988] showed 2 or more positive serum autoantibody titers in 9.3% of MD patients, the commonest being antinuclear autoantibody (23.3% of patients).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported the high frequency of nonspecific autoantibodies in 50-70% of the patients with MD, with the anti-nuclear antibodies being the most common [19,20]. Since autoantibodies are frequently detected in chronic inflammatory disorders with infectious origin, the high frequency of these autoantibodies in MD suggests a secondary autoimmune process induced by a persisting infectious agent.…”
Section: Discussionmentioning
confidence: 99%